Effects of Controlled Culture Conditions on Chemical Composition and Antimicrobial Activities of Mentha rotundifolia Essential Oils - Benahmed, Amira; Cherouana, Khaoula; Benchikhelhocine, Imen; Ikhlef, Assia; Meghezzi, Asma; Harfi, Boualem (Journal of Pharmacy and Nutrition Sciences, 2022)
The study objectives were the determination of Mentha rotundifolia essential oils composition using GC/MS analysis and the evaluation of their antimicrobial activities. In addition, the determination of the relationships between plants acclimatization conditions, essential oils composition and antimicrobial activities. Essential oils extracted via hydrodistillation method from wild plants and acclimatized plants in different culture conditions of Mentha rotundifolia. Five selected pathogenic microbial strains were used to evaluate EOs in vitro antimicrobial activities. Essential oils GC/MS analysis revealed the dominance of the oxygenated monoterpene (piperitenone oxide). A significant effect of plant culture conditions in acclimatization room on essential oils composition compared to the control was observed. We also noted that antimicrobial activities of extracted essential oils from acclimatized plants were higher than those from field-grown M. rotundifolia plants. Content of Piperitenone Oxide in acclimatized plantlets is 93.07% for plantlets cultured at 16°C and a photoperiod of 16 hours light / 8 hours dark, statistically higher than wild plants where it is around 78%. We also noted the presence of Limonene (5.7%) in plantlets grown at 35°C which is significantly different than that of the wild plants (1.55 %). Essential oils antimicrobial activities showed that the plantlets grown at 16 °C or in total darkness were more active towards the tested strains. While, the EO of plantlets cultured at 35 °C were the least active.